PERCEIVED SELF EFFICACY TO COPE WITH EARTHQAKUES - Lopez, Ernesto; Morales-Martinez, Guadalupe Elizabeth; Yanko Norberto ,; Patino-Munguia, Luis Rodolfo (Advances in Social Sciences Research Journal, 2019)
A sample of 155 Mexican participants who experienced severe earthquakes was required to read a set of 32 scenarios each describing a hypothetical earthquake scenario. After reading a scenario, participants judged their own self efficacy to deal with the described scenario. Analysis of results from an information integration theory approach showed that all participants can be grouped into four clusters. Participants of three clusters used a summative cognitive rule to integrate information of location, magnitude of seismic activity, earthquake type and other people´s reactions to the earthquake. Here, magnitude and other people´s reactions were the most relevant, but these factors had different valuation through cognitive ruled groups. Location and civil protection indications were relevant to groups having moderate and low self-efficacy to cope with disaster. Thus, systematic integration of information from scenarios and differential valuation of factors relate to judgment formation producing different degrees self-efficacy to cope with disaster.